Pemanfaatan Media Electronic sebagai Upaya Meningkatkan Pemahaman Peserta Didik dalam Pembelajaran Sejarah Kebudayaan Islam - Istiqomah, Nurul; Mahbubi, M (CENDEKIA, 2024)
This research aims to describe using electronic media to improve students' understanding, especially in learning Islamic Cultural History. The method used in this research is the descriptive qualitative method, which is a technique used in data collection through observation, interviews, and documentation. To determine the validity of the data, researchers triangulated data sources to check data and compare data. The results showed that the implementation of LED TV electronic media in the learning process of Islamic Cultural History uses two features, namely visual and audiovisual. In the implementation process, the presentation of material through PowerPoint, video content, movies, pictures, and others. In addition to audiovisual viewing, teaching staff also conduct short discussions which are carried out as a form of strengthening students' memory of learning material. By utilizing this electronic media, teachers can provide a more real understanding to students and be able to improve students' memory.